Notch signaling regulates the responses of lipopolysaccharide-stimulated macrophages in the presence of immune complexes. - Wipawee Wongchana; Pornrat Kongkavitoon; Pattarin Tangtanatakul; Chutamath Sittplangkoon; Patcharavadee Butta; Supatta Chawalitpong; Thitiporn Pattarakankul; Barbara A Osborne; Tanapat Palaga (PLoS ONE)
Macrophages exhibit diverse effector phenotypes depending on the stimuli and their microenvironment. Classically activated macrophages are primed with interferon (IFN)γ and stimulated with pathogen-associated molecular patterns. They produce inflammatory mediators and inflammatory cytokines, such as IL-12. In the presence of immune complexes (ICs), activated macrophages have decreased IL-12 production and increased IL-10 production and presumably act as regulatory macrophages. Notch signaling has been shown to regulate the effector functions of classically activated macrophages. In this study, we investigated whether Notch signaling is active in lipopolysaccharide (LPS)-stimulated macrophages in the presence of ICs. LPS/IC stimulation increased the level of cleaved Notch1 in murine macrophages, while IC stimulation alone did not. Delta-like 4, but not Jagged1, was responsible for generating cleaved Notch1. The activation of Notch signaling by LPS/ICs depended upon NF-κB and MEK/Erk pathway activation. Macrophages with the targeted deletion of Rbpj, which encodes a DNA-binding protein central to canonical Notch signaling, produced significantly less IL-10 upon LPS/IC stimulation. A similar impact on IL-10 production was observed when Notch signaling was inhibited with a gamma-secretase inhibitor (GSI). Defects in NF-κB p50 nuclear localization were observed in GSI-treated macrophages and in Rbpj-/- macrophages, suggesting cross-regulation between the Notch and NF-κB pathways. Transcriptomic analysis revealed that Notch signaling regulates the transcription of genes involved in the cell cycle, macrophage activation, leukocyte migration and cytokine production in LPS/IC-stimulated macrophages. Taken together, these results suggest that the Notch signaling pathway plays an important role in regulating the functions of macrophages activated by LPS and ICs.